The Pastoral Priority Principle in Catholic Religious Education: Balancing Curriculum and Faith Formation - Hetbin Jefrianto Marbun (FOCUS, 2026)
This study reflects on the tension between curriculum requirements and faith formation needs in the implementation of Catholic Religious Education (CRE) for public school students who participate in parish-based faith formation programs. The study employs a qualitative approach using a practice-based pastoral reflection method. The data derive from one year of CRE accompaniment in a parish within the Diocese of Bandung, Indonesia. The study enriches these data through participant observation, documentation of pastoral experiences, and informal conversations with fellow volunteer catechetical companions. The analysis engages Church documents, Paulo Freire’s critical pedagogy, and perspectives from inclusive education. The findings show that learners demonstrate substantial diversity in academic ability, literacy skills, and mastery of foundational elements of the Catholic faith. This diversity often prevents the curriculum from being implemented linearly according to its intended sequence and objectives. In practice, companions consistently adjust instruction by postponing certain topics, simplifying learning objectives, strengthening foundational faith formation, and adapting teaching methods to learners’ actual needs. These findings indicate that decision-making in Catholic Religious Education involves not only pedagogical considerations but also a process of pastoral discernment. The study’s primary contribution is the development of the Pastoral Priority Principle, a principle that places the needs most conducive to learners’ faith growth at the center of decision-making when curriculum requirements and learners’ actual conditions cannot be addressed simultaneously.